2016
DOI: 10.1016/j.cell.2016.02.046
|View full text |Cite
|
Sign up to set email alerts
|

The Antagonistic Gene Paralogs Upf3a and Upf3b Govern Nonsense-Mediated RNA Decay

Abstract: SUMMARY Gene duplication is a major evolutionary force driving adaptation and speciation, as it allows for the acquisition of new functions and can augment or diversify existing functions. Here, we report a gene duplication event that yielded another outcome – the generation of antagonistic functions. One product of this duplication event – UPF3B – is critical for the nonsense-mediated RNA decay (NMD) pathway, while its autosomal counterpart – UPF3A – encodes an enigmatic protein previously shown to have trace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
237
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 135 publications
(250 citation statements)
references
References 43 publications
(80 reference statements)
9
237
4
Order By: Relevance
“…However, although the studies by Shum and coworkers and Bao and coworkers reported the essential role of NMD in spermatogenesis, the importance of CB-localization for the function of these NMD factors remains to be investigated (Bao et al 2016, Shum et al 2016. Important support for the involvement of CB in the NMD pathway comes from a study by Fanourgakis and cowkorkers (Fanourgakis et al 2016).…”
Section: R86mentioning
confidence: 92%
See 4 more Smart Citations
“…However, although the studies by Shum and coworkers and Bao and coworkers reported the essential role of NMD in spermatogenesis, the importance of CB-localization for the function of these NMD factors remains to be investigated (Bao et al 2016, Shum et al 2016. Important support for the involvement of CB in the NMD pathway comes from a study by Fanourgakis and cowkorkers (Fanourgakis et al 2016).…”
Section: R86mentioning
confidence: 92%
“…However, a massive depletion of both spermatocytes and spermatids was observed, which resulted in the absence of spermatozoa in the epididymis. Interestingly, the deletion of NMD repressor Upf3a, but not Upf3b, led to spermatogenic failure in mice (Shum et al 2016). Therefore, the correct balance between the NMD factors and NMD repressors appears to be important for the proper progression of spermatogenesis.…”
Section: Chromatoid Body and Nonsense-mediated Mrna Decaymentioning
confidence: 99%
See 3 more Smart Citations